PENERAPAN BUDAYA LITERASI UNTUK MEMBENTUK KARAKTER SISWA GEMAR MEMBACA - Dinda Adelia Litasar; Rofian; Choirul Huda (STKIP Subang, 2023)
The background that drives this research is that there are students who are less fluent and interested in reading at SD N 2 Burikan, this is because students tend to use cellphones more often than doing reading activities. The problems in this study are 1) How is the implementation of the literacy culture of characters like to read in the teaching campus program 4 at SD N 2 Burikan Kudus?, 2) How is the impact of the application of the literacy culture of characters like to read in the teaching campus program 4 at SD N 2 Burikan Kudus?. The objectives to be achieved in this study are 1) Describing the implementation of the literacy culture of characters who like to read through the Teaching Campus 4 program at SD N Burikan 2 Kudus. 2) Knowing the impact of implementing a culture of literacy for characters like to read through the Teaching Campus 4 program at SD N 2 Burikan Kudus. This type of research is qualitative research. The study population is all grade III students of SD N 2 Burikan for the 2022/2023 academic year. The samples taken were grade III students, homeroom teachers and the principal of SD N 2 Burikan for interviews. For this sampling are selected with high, medium, low categories. The data in this study was obtained through observation, interviews, questionnaires, and documentation. The results of the analysis of the application of reading literacy culture and based on the results of interviews show that literacy activities held in schools are very helpful for improving students' reading skills. Literacy activities carried out every day at SD N 2 Burikan can also develop student character, especially in reading.